The profitability of telecommunication companies in Malaysia / Muhammad Faiz Amli - Amli, Muhammad Faiz (2019)
The telecommunication sector in Malaysia has grown significantly over the last few decades. The analysis is to determine the profitability of telecommunication companies in Malaysia with a specific focus on the size(SIZE), leverage(LEV) and liquidity(LIQ) . The data for '•"-T intrepreted is collected from annual report and the measurement of total asset, debt to equity and current ratio are used to see the overall profitability of telecommunication companies in Malaysia within 9 years. This study get the data period from 2009 until 2017. Secondary data and Pooled Ordinary Least Square (POLS) regression model are used to analyze the result or finding.To identified the profitability of telecommunication companies the year depends on independent variable. I can conclude that the liquidity(LIQ) and size of companies(SIZE) is negative and significant relationship with the profitability of Telecommunication companies in Malaysia. Meanwhile, leverage(LEV) is positive and significant relationship with the profitability(ROA) of Telecommunication companies in Malaysia.